"The Present of Things Future" in Fiction - E. Morse, Donald (FOCUS: Papers in English Literary and Cultural Studies, 2024)
We cannot speak meaningfully of the future without taking into consideration the past and the present. Of those scholars or thinkers who have discoursed on the relation of the past to the present to the future, few have done so as cogently or as memorably as Saint Augustine in Chapter XI of his Confessions. There, he ponders over the question, “What is time?” concluding: What then is time? I know what it is if no one asks me what it is; but if I want to explain it to someone who has asked me, I find that I do not know. Nevertheless, I can confidently assert that I know this: that ifnothing passed away there would be no past time, and if nothing were coming there would be no future time, and if nothing were now there would be no present time. (XI: 14, 267).